Synergy between the Faculty of Da'wah and Communication, Unisnu Jepara and the Management of the Special Branch of Fatayat NU Malaysia in Empowering the Da'wah of Aswaja An-Nahdliyyah - Wahab, Abdul; Muslimin, Khoirul; Haqqi, Muhammad Nashrul; Fajrie, Mahfudlah; Murniati, Murniati; Oktafian, Ananda Wahyu; Suroso, Suroso; Inah, Inah (Universitas Islam Nahdlatul Ulama Jepara, 2024)
This community service was carried out between the Faculty of Da'wah and Communication, Unisnu Jepara and PCI Fatayat NU Malaysia. There are three aspects to the problem of this service: 1) The world's need for Da'wah in the style of Ahlis Sunnah wal Jama'ah; 2) The need for empowering resources and human resources related to materials, strategies, media, recognition and opportunities for preaching in the style of Ahlis Sunnah wal Jama'ah; 3) Empowering skills, initiation, innovation, collaboration opportunities, communication and problem solving formulations for Islamic da'wah problems that occur in parts of the world, so that Ahlis Sunnah wal Jama'ah style da'wah can become a universal movement. Through community service, the solutions offered are 1) Forming a